Game-Based eHealth Interventions for the Reduction of Fatigue in People With Chronic Diseases: Systematic Review and Meta-Analysis - Leonie S Warlo; Souraya El Bardai; Andrica de Vries; Marie-Lise van Veelen; Suzan Moors; Edmond HHM Rings; Jeroen S Legerstee; Bram Dierckx (JMIR Publications, 2024)
BackgroundFatigue is a common and debilitating side effect of chronic diseases, significantly impacting patients' quality of life. While physical exercise and psychological treatments have been shown to reduce fatigue, patients often struggle with adherence to these interventions in clinical practice. Game-based eHealth interventions are believed to address adherence issues by making the intervention more accessible and engaging. ObjectiveThis study aims to compile empirical evidence on game-based eHealth interventions for fatigue in individuals with chronic diseases and to evaluate their effectiveness in alleviating fatigue. MethodsA comprehensive literature search was performed across Embase, MEDLINE ALL, PsycINFO, Web of Science Core Collection, Cochrane Central Register of Controlled Trials, and Google Scholar in August 2021. Study characteristics and outcomes from the included studies were extracted, and a random-effects meta-analysis was conducted. Sensitivity and subgroup analyses were performed to identify sources of heterogeneity. ResultsOf 1742 studies identified, 17 were included in the meta-analysis. These studies covered 5 different chronic diseases: multiple sclerosis (n=10), cancer (n=3), renal disease (n=2), stroke (n=1), and Parkinson disease (n=1). All but 1 study used exergaming interventions. The meta-analysis revealed a significant moderate effect size in reducing fatigue favoring the experimental interventions (standardized mean difference [SMD] -0.65, 95% CI -1.09 to -0.21, P=.003) compared with control conditions consisting of conventional care and no care. However, heterogeneity was high (I2=85.87%). Subgroup analyses were conducted for the 2 most prevalent diseases. The effect size for the multiple sclerosis subgroup showed a trend in favor of eHealth interventions (SMD -0.47, 95% CI -0.95 to 0.01, P=.05, I2=63.10%), but was not significant for the cancer group (SMD 0.61, 95% CI -0.36 to 1.58, P=.22). Balance exercises appeared particularly effective in reducing fatigue (SMD -1.19, 95% CI -1.95 to -0.42, P=.002). ConclusionsGame-based eHealth interventions appear effective in reducing fatigue in individuals with chronic diseases. Further research is needed to reinforce these findings and explore their impact on specific diseases. Additionally, there is a lack of investigation into interventions beyond exergaming within the field of game-based learning.